Interface engineering of a noble-metal-free 2D–2D MoS2/Cu-ZnIn2S4 photocatalyst for enhanced photocatalytic H2 production. Issue 30 (21st July 2017) - Yuan, Yong-Jun; Chen, Daqin; Zhong, Jiasong; Yang, Ling-Xia; Wang, Jingjing; Liu, Mei-Jiao; Tu, Wen-Guang; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract : A 2D–2D MoS2 /Cu-ZnIn2 S4 nanocomposite is designed as a highly efficient noble-metal-free photocatalyst for solar H2 generation. Abstract : Accelerating the charge separation of semiconductor photocatalysts remains a great challenge to develop highly efficient solar-to-H2 conversion systems. Here, 2D Cu 2+ -doped ZnIn2 S4 (Cu-ZnIn2 S4 ) nanosheets modified with 2D MoS2 are designed and prepared via solution chemical routes. Detailed characterization reveals that the specially designed unique 2D–2D structure is critical to the high photocatalytic performance for solar H2 generation. Benefiting from the presence of a large 2D nanojunction in the 2D–2D photocatalyst, the MoS2 /Cu-ZnIn2 S4 has an increased contact surface area for charge transfer. The improved charge separation is demonstrated by the significant enhancement of photocurrent responses. It is found that the 2D–2D MoS2 /Cu-ZnIn2 S4 photocatalyst at a 6 wt% MoS2 loading amount exerts a 5463 μmol h −1 g −1 H2 -evolution rate under visible light irradiation ( λ > 420 nm) with an apparent quantum yield of 13.6% at wavelength λ = 420 nm in 0.1 M ascorbic acid aqueous solution. This activity far exceeds those of noble metal (such as Pt, Ru, Pd or Au) loaded-Cu-ZnIn2 S4 photocatalysts. The results demonstrate that the construction of a 2D nanojunction is a promising strategy to accelerate charge separation and enhance the photocatalytic performance of semiconductor photocatalysts for solar H2 generation.